Human risk of diseases associated with red meat intake: Analysis of current theories and proposed role for metabolic incorporation of a non-human sialic acid. (October 2016) - Alisson-Silva, Frederico; Kawanishi, Kunio; Varki, Ajit
Abstract: One of the most consistent epidemiological associations between diet and human disease risk is the impact of red meat consumption (beef, pork, and lamb, particularly in processed forms). While risk estimates vary, associations are reported with all-cause mortality, colorectal and other carcinomas, atherosclerotic cardiovascular disease, type II diabetes, and possibly other inflammatory processes. There are many proposed explanations for these associations, some long discussed in the literature. Attempts to explain the effects of red meat consumption have invoked various red meat-associated agents, including saturated fat, high salt intake, Trimethylamine–N-oxide (TMAO) generation by microbiota, and environmental pollutants contaminating red meat, none of which are specific for red meat. Even the frequently mentioned polycyclic aromatic carcinogens arising from high temperature cooking methods are not red meat specific, as these are also generated by grilling poultry or fish, as well as by other forms of cooking. The traditional explanations that appear to be more red meat specific invoke the impact of N- nitroso compounds, heme iron, and the potential of heme to catalyze endogenous nitrosation. However, heme can be denatured by cooking, high levels of plasma hemopexin will block its tissue delivery, and much higher amounts of heme likely originate from red blood cell breakdown in vivo . Therefore, red meat-derived heme could only contribute to colorectal carcinoma risk, via direct local effects. Also, none of these mechanisms explain the apparent human propensity i.e., other carnivores have not been reported at high risk for all these diseases. A more recently proposed hypothesis involves infectious agents in beef from specific dairy cattle as agents of colorectal cancer. We have also described another mechanistic explanation for the human propensity for risk of red-meat associated diseases that is consistent with most observations: metabolic incorporation of a non-human sialic acid N -glycolylneuraminic acid (Neu5Gc) into the tissues of red meat consumers and the subsequent interaction with inflammation-provoking antibodies against this "xenoautoantigen". Overall, we conclude that while multiple mechanisms are likely operative, many proposed theories to date are not specific for red meat, and that the viral and xenoautoantigen theories deserve further consideration. Importantly, there are potential non-toxic dietary antidotes, if the xenoautoantigen theory is indeed correct.